2021
DOI: 10.3389/fpsyt.2021.655802
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chronic Spontaneous Urticaria With Anxiety and Depression in Adolescents: A Mediation Analysis

Abstract: Background: Chronic spontaneous urticaria (CSU) is related to psychiatric comorbidities. It is not clear whether the relationship is affected by modifiable factors.Objectives: To investigate whether the effect of CSU on anxiety and depression in adolescents is mediated by the symptoms of itching and sleep disturbance.Methods: Questionnaire survey was conducted among newly enrolled college students. Dermatologists diagnose skin diseases, including CSU, during health examination. Anxiety and depression were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study by Hamam suggested that physicians treating patients with hypertension should be aware of the role that anxiety and depression play in treatment efficacy and compliance [39]. Several studies have revealed that patients with CSU frequently have anxiety and depression, which are probably exacerbated by the symptoms of itching and sleep disturbance [40][41][42][43]. Studies have suggested that acupuncture treatment can alleviate anxiety and depression [44][45][46][47], which may benefit patients with CSU by decreasing the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Hamam suggested that physicians treating patients with hypertension should be aware of the role that anxiety and depression play in treatment efficacy and compliance [39]. Several studies have revealed that patients with CSU frequently have anxiety and depression, which are probably exacerbated by the symptoms of itching and sleep disturbance [40][41][42][43]. Studies have suggested that acupuncture treatment can alleviate anxiety and depression [44][45][46][47], which may benefit patients with CSU by decreasing the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Skin diseases for which correlations between the occurrence of the disease and/or the severity of skin symptoms and psychological factors such as anxiety or depression have been shown include—but are not limited to—atopic dermatitis, psoriasis, chronic urticaria and prurigo 12–17 . Also, there is a relationship between psychological stress and the occurrence and exacerbation of symptoms of various skin diseases 18–21 .…”
Section: What Is Psychodermatology?mentioning
confidence: 99%
“…7,10,11 Skin diseases for which correlations between the occurrence of the disease and/or the severity of skin symptoms and psychological factors such as anxiety or depression have been shown include-but are not limited to-atopic dermatitis, psoriasis, chronic urticaria and prurigo. [12][13][14][15][16][17] Also, there is a relationship between psychological stress and the occurrence and exacerbation of symptoms of various skin diseases. [18][19][20][21] It is supposed that under stress patients with skin disorders develop dysfunctional coping such as catastrophizing thoughts, which may contribute, on one hand, to a worsening of the disease, and on the other hand, to higher suicidality rates.…”
Section: W H At Is Psych Ode R M a Tol Ogy ?mentioning
confidence: 99%
“…Patients with CSU experience higher rates of anxiety and depression relative to healthy controls [ 36 , 37 ], which is linked to emotional distress [ 38 ] and increased impairment in QoL [ 39 ]. As an explanation, a mediation model proposed that anxiety and depression develop because itching associated with CSU leads to sleep disturbance [ 40 ], which is associated with risk of depression [ 41 ] and anxiety [ 42 ].…”
Section: What Is Csu?mentioning
confidence: 99%